EXPLORING ENGLISH PROFICIENCY LEVELS OF INDONESIAN UNIVERSITY STUDENTS THROUGH ENGLISHSCORE BASED ASSESSMENT - Diah Kurniati; Ahdi Riyono; Achmad Solaeman; Arceli R. Millan; Nooreen Noordin (University of Kuningan, 2025)
English language proficiency is a critical competency for university students in Indonesia, serving as a gateway to academic achievement, global engagement, and professional advancement. Despite its importance, limited empirical data exist on students' actual proficiency levels, especially through mobile-based assessments designed to reflect real-world language use in context. This study investigates the English proficiency of Indonesian undergraduate students using the EnglishScore mobile application—an internationally recognized assessment tool that differs from traditional exams like TOEFL or IELTS by offering short, adaptive, and skills-specific tests accessible via smartphones. Utilizing a quantitative descriptive design, the study assessed 1.216 students from various departments on grammar, vocabulary, reading, and listening, aligned with CEFR standards. Results show that 55% of students are at A1, 28% at A2, 12% at B1, and only 3% at B2. These findings reveal a substantial gap between expected and actual proficiency levels after years of formal instruction. The research highlights the urgent need for universities to adopt communicative, proficiency-oriented curricula and leverage mobile-based diagnostics to inform instruction. Mobile tools like EnglishScore, which mirror authentic language use by simulating everyday communicative tasks, offer scalable, low-barrier alternatives for assessment. This study contributes to the underexplored area of digital language testing in Indonesia and provides actionable insights for policymakers and educators to enhance language learning strategies through technology-informed policy and pedagogy.